We must take a One Health approach to improve pandemic infection control. (19th October 2020) - Benfield, Camilla TO; Heymann, David; Clark, Judy MacArthur; Trees, AJ; Sethia, Babulal
Abstract : The Covid-19 pandemic must serve as a wake-up call to work more collaboratively between medical and veterinary practitioners, biologists and environmentalists say Camilla Benfield, David Heymann, Judy MacArthur Clark, AJ Trees and Babulal Sethia